Optimizing Early Childhood Sensorimotor Development through Nature-Based Art Activities: A Case Study at Tarbiyatul Islamiyah Playgroup - Habibatul Karimah; Umi Masturoh (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to describe the implementation of nature-based art activities and identify the supporting and inhibiting factors in optimizing the sensorimotor development of early childhood at Tarbiyatul Islamiyah Playgroup. This study employed a qualitative descriptive approach using a case study design. The research participants consisted of 20 playgroup children aged 3–4 years and their classroom teacher. Data were collected through participatory observation, in-depth interviews, and documentation of the children's work. The data were analyzed qualitatively using the interactive model of data reduction, data display, and conclusion drawing. The findings revealed that nature-based art activities, including threading papaya leaf stalks, modeling with clay, and creating collages from seeds, effectively stimulated hand–eye coordination, fine motor strength, sensory sensitivity, concentration, and children's independence. Supporting factors included the availability of natural materials within the school environment, teachers' creativity, children's enthusiasm, and parental support. Meanwhile, the inhibiting factors comprised limited instructional time, differences in children's motor abilities, inadequate facilities, and limited teacher training related to nature-based art activities. The findings confirm that nature-based art activities constitute an innovative and contextual learning strategy that effectively supports the optimization of sensorimotor development in early childhood education.